Which Is the Optimum Antigen Concentration for the Venereal Disease Research Laboratory Test of Cerebrospinal Fluid for Neurosyphilis Diagnosis: 10 or 17 μL? - Xiao, Yao; Li, Wei; Li, Qiu-Ling; Xu, Qiu-Yan; Yang, Yang; Yang, Tian-Ci; Liu, Li-Li; Gu, Wei-Ming (Frontiers in Medicine, 2022)
The manufacturer's instructions for the venereal disease research laboratory (VDRL) antigen test for diagnosing neurosyphilis describe testing of serum samples and do not include procedures for cerebrospinal fluid (CSF) testing. This study compared the CSF-VDRL test with 10 μL of antigen (CSF-VDRL-10) according to the American Public Health Association to the CSF-VDRL test with 17 μL of antigen (CSF-VDRL-17) according to the VDRL serum procedure. A total of 121 neurosyphilis patients and 86 syphilis/non-neurosyphilis patients were included. The sensitivities of the CSF-VDRL-10 and CSF-VDRL-17 tests were comparable for neurosyphilis diagnosis. The positive rate of the CSF-VDRL-17 test was higher than that of the CSF-VDRL-10 test. In all, 78.3% of the quantitative CSF-VDRL-17 results were consistent with those of the CSF-VDRL-10 test, 18.4% exhibited one-titer higher results than those of the CSF-VDRL-10 test, and 3.4% had positive CSF-VDRL-17 results but negative CSF-VDRL-10 results. The CSF-VDRL test with 17 μL of antigen was more sensitive, and it is worth performing longitudinal studies to understand its practical implications.